Hypotensive Epidural Anesthesia in Patients With Aortic Stenosis Undergoing Total Hip Replacement. Issue 2 (1st February 2008) - Ho, Michael C.; Beathe, Jonathan C.; Sharrock, Nigel E.
Abstract : Background and Objectives: The use of conduction anesthesia and induced hypotension are traditionally contraindicated in patients with aortic stenosis. This hypothesis-generating observational pilot study details the clinical outcomes in patients with aortic stenosis undergoing hypotensive epidural anesthesia for total hip replacement. Methods: From a database of 1, 947 consecutive patients undergoing total hip replacement under hypotensive epidural anesthesia performed from 1994 to 2005, 22 patients were identified with aortic stenosis. Chart review was performed. All patients were monitored with central venous pressure and radial arterial catheters. Cardiovascular and renal outcomes, thromboembolic events, and blood loss and transfusion were assessed. Results: Twenty-two patients were identified: 19 patients (86%) were American Society of Anesthesiologists classification III, and 3 patients (14%) were American Society of Anesthesiologists classification IV. The mean age was 75 years (range: 58-92). No patient suffered from preoperative angina, syncope, or resting dyspnea. Valve areas ranged from 0.9 to 1.8 cm 2 and peak gradient from 12 to 64 mm Hg. Systolic blood pressure was maintained at 60 to 100 mm Hg. The mean duration of hypotension was 91 minutes (range: 50-200). Heart rate was maintained at a mean (±SD) of 70 ± 11. Central venous pressure was maintained at baseline value. Mean intraoperative crystalloid administered was 1, 695 mL (range: 900-4, 000), and mean estimated blood loss was 234 mL (range: 100-1, 500). There were no deaths, myocardial infarctions, cerebrovascular accidents, or pulmonary embolic events. No patient developed renal dysfunction. Conclusions: We report the absence of complications (with calculated upper limit 95% confidence interval of approximately 13.6%) when hypotensive epidural anesthesia was performed in 22 patients with noncritical asymptomatic aortic stenosis.